215k views
13 votes
The multipliers that will create opposite terms of the y-variable for this system have been determined. Use the equivalent system of equations to solve the system. 4(3x − 1 4 y = 15) → 12x − y = 60 −6(2 3 x − 1 6 y = 6) → − 4x + y = − 36 What is the solution to the system of equations? ( , )

User JosephHirn
by
6.0k points

2 Answers

11 votes

Answer:

3 -24

Explanation:

got it right

User Anran Zhang
by
6.0k points
12 votes

Answer:

The answer to the multipliers that will create opposite terms of the y-variable for this system have been determined. Use the equivalent system of equations to solve the system. is (3, -24)

Explanation:

User John Von Neumann
by
5.4k points